Twelve-month and lifetime prevalence and lifetime morbid risk of anxiety and mood disorders in the United States - Kessler, Ronald C.; Petukhova, Maria; Sampson, Nancy A.; Zaslavsky, Alan M; Wittchen, Hans-Ullrich (International journal of methods in psychiatric research, 2012)
Estimates of 12‐month and lifetime prevalence and of lifetime morbid risk (LMR) of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM‐IV‐TR) anxiety and mood disorders are presented based on US epidemiological surveys among people aged 13+. The presentation is designed for use in the upcoming DSM‐5 manual to provide more coherent estimates than would otherwise be available. Prevalence estimates are presented for the age groups proposed by DSM‐5 workgroups as the most useful to consider for policy planning purposes. The LMR/12‐month prevalence estimates ranked by frequency are as follows: major depressive episode: 29.9%/8.6%; specific phobia: 18.4/12.1%; social phobia: 13.0/7.4%; post‐traumatic stress disorder: 10.1/3.7%; generalized anxiety disorder: 9.0/2.0%; separation anxiety disorder: 8.7/1.2%; panic disorder: 6.8%/2.4%; bipolar disorder: 4.1/1.8%; agoraphobia: 3.7/1.7%; obsessive‐compulsive disorder: 2.7/1.2. Four broad patterns of results are most noteworthy: first, that the most common (lifetime prevalence/morbid risk) lifetime anxiety‐mood disorders in the United States are major depression (16.6/29.9%), specific phobia (15.6/18.4%), and social phobia (10.7/13.0%) and the least common are agoraphobia (2.5/3.7%) and obsessive‐compulsive disorder (2.3/2.7%); second, that the anxiety‐mood disorders with the earlier median ages‐of‐onset are phobias and separation anxiety disorder (ages 15–17) and those with the latest are panic disorder, major depression, and generalized anxiety disorder (ages 23–30); third, that LMR is considerably higher than lifetime prevalence for most anxiety‐mood disorders, although the magnitude of this difference is much higher for disorders with later than earlier ages‐of‐onset; and fourth, that the ratio of 12‐month to lifetime prevalence, roughly characterizing persistence, varies meaningfully in ways consistent with independent evidence about differential persistence of these disorders. Copyright © 2012 John Wiley & Sons, Ltd.